TEMPERATURE CHANGE IS THE MAJOR DRIVER OF LATE-GLACIAL AND HOLOCENE GLACIER FLUCTUATIONS IN NEW ZEALAND - Anderson B.; Mackintosh A. (My University, 2006)
Advance and retreat of temperate glaciers is largely controlled by changes in temperature and precipitation, but the relative importance of these drivers is debated. Numerical modeling of a New Zealand glacier reveals that temperature is the dominant control on glacier length. We find that a glacial advance, dated to ca. 13,000 yr B.P., requires a cooling event of 3-4 °C. This mid-latitude Southern Hemisphere cooling is similar in magnitude to the Antarctic Cold Reversal in the Vostok ice core record and likely to be a response to the same climate signal. © 2006 Geological Society of America.
Keywords: GLACIERS; LITTLE ICE AGE; NEW ZEALAND; SOUTHERN HEMISPHERE; YOUNGER DRYAS; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен